Self-Administered Ethanol Enema Causing Accidental Death. (11th November 2014) - Peterson, Thomas; Rentmeester, Landen; Judge, Bryan S.; Cohle, Stephen D.; Jones, Jeffrey S.
Abstract : Excessive ethanol consumption is a leading preventable cause of death in the United States. Much of the harm from ethanol comes from those who engage in excessive or hazardous drinking. Rectal absorption of ethanol bypasses the first pass metabolic effect, allowing for a higher concentration of blood ethanol to occur for a given volume of solution and, consequently, greater potential for central nervous system depression. However, accidental death is extremely rare with rectal administration. This case report describes an individual with klismaphilia whose death resulted from acute ethanol intoxication by rectal absorption of a wine enema.